The value of circulating lymphocytic subpopulations in the diagnosis and repair of ischemic stroke patients with dizziness - Wang, Yong; Huang, Yichen; Li, Sicheng; Lin, Jixian; Liu, Yang; Gao, Yanqin; Zhao, Jing (Frontiers in Aging Neuroscience, 2022)
Background: To determine whether dizziness can contribute to stroke as a main cause still remains challenging. This study aims to explore clinical biomarkers in the identification of ischemic stroke patients from people with dizziness and the prediction of their long-term recovery. Methods: From January 2018 to June 2019, 21 ischemic stroke patients with a main complaint of dizziness, 84 non-stroke dizziness patients and 87 healthy volunteers were recruited in this study. Then, their peripheral blood samples were collected, and the percentages of circulating lymphocytes T cells, CD4+ T cells, CD8+ T cells, T-/- cells (DNTs), CD4+ regulatory T cells (Tregs), CD8+ Tregs, B cells and regulatory B cells (Bregs) were examined to identify biomarkers with clinical value. Results: According to our data, a significant difference in the DNTs proportion was detected between non-stroke dizziness and ischemic stroke patients with dizziness (P=0.0009). The Bregs proportion in ischemic stroke patients with dizziness was lower than that in non-stroke dizziness patients (P=0.035). In addition, the percentage of Bregs and DNTs within lymphocytes in patients' peripheral blood exhibited a significant negative correlation with stroke occurrence (Bregs, P=0.039; DNTs, P=0.046). Moreover, the Bregs and DNTs within lymphocytes were negatively related to participants’ age, while presented a weak relationship with clinical risks like smoking, hypertension, and diabetes. Then, area under the receiver operating characteristic curve (AUC) of Bregs and DNTs together was 0.768, the risk factors and Bregs or DNTs ranged from 0.795 and 0.792, respectively, and the AUC value of risk factors, Bregs and DNTs combination was further increased to 0.815. Furthermore, the Bregs percentage within lymphocytes at admission was also a potential predictor of repair at discharge and the following 3 months. Conclusion: Bregs and DNTs could be the clinical biomarkers together in the identification of ischemic stroke patients from people with dizziness.